Interleukin-10 haplotypes are not associated with acute cerebral ischemia or high-risk transcranial Doppler in a newborn cohort of 395 children with sickle cell anemia - Belisário,André Rolim (2017)
ABSTRACT Background: The etiology of stroke, a severe complication of sickle cell anemia, involves inflammatory processes. However, the pathogenetic mechanisms are unknown. The aim of this study was to evaluate the influence of interleukin-10 polymorphisms and haplotypes on the risk of acute cerebral ischemia and high-risk transcranial Doppler in 395 children with sickle cell anemia from the state of Minas Gerais, Brazil. Methods: Interleukin-10 haplotypes were determined by polymerase chain reaction-restriction fragment length polymorphism and sequencing. The outcomes studied were acute cerebral ischemia and high-risk transcranial Doppler. Clinical data were retrieved from the children's records. Results: There was no statistically significant difference in the frequencies of polymorphisms and haplotypes between children with and without acute cerebral ischemia or children with or without high-risk transcranial Doppler. These data are consistent with a previous report that showed an absence of association between interleukin-10 plasma levels and high-risk transcranial Doppler velocity in children with sickle cell anemia. Conclusion: Interleukin-10 haplotypes were not associated with the risk of acute cerebral ischemia or high-risk transcranial Doppler velocity in children with sickle cell anemia from the state of Minas Gerais, Brazil.